2022
DOI: 10.1101/2022.10.07.511138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast burst fraction transients convey information independent of the firing rate

Abstract: Theories of attention and learning have hypothesized a central role for high-frequency bursting in cognitive functions, but experimental reports of burst-mediated representations in vivo have been limited. Here we used a novel demultiplexing approach to separate independent streams of information from considering neurons as having three possible states: silent, singlet- and burst-firing. We studied this ternary neural code in vivo while animals learned to behaviorally report direct electrical stimulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 68 publications
(126 reference statements)
1
7
0
Order By: Relevance
“…Consistently, Takahashi et al (2016) found that cells responding with a higher burst fraction were more likely to be predictive of the animal's perceptual report than cells with a lower burst fraction. Averaging over a population of cells, Naud et al (2022) showed that micro-stimulation induced increases in burst fraction over a population of cells. This change in burstiness adapted over multiple days, coming earlier as the animal became better at the detection task.…”
Section: Bursting In Vivomentioning
confidence: 99%
See 4 more Smart Citations
“…Consistently, Takahashi et al (2016) found that cells responding with a higher burst fraction were more likely to be predictive of the animal's perceptual report than cells with a lower burst fraction. Averaging over a population of cells, Naud et al (2022) showed that micro-stimulation induced increases in burst fraction over a population of cells. This change in burstiness adapted over multiple days, coming earlier as the animal became better at the detection task.…”
Section: Bursting In Vivomentioning
confidence: 99%
“…Furthermore, if bursting controls plasticity by providing a unit-specific representation of error Payeur et al (2021), one would predict that the relevant period for this instructive signal to act would come after any cues are given and after reward delivery or lack thereof. An increase in burstiness has been shown to encode errors with a delay of about 1 s with respect to the cue (Naud et al, 2022), suggesting that second-long eligibility traces similar to hippocampus may be at work in cortex. Consistently silencing pyramidal cell activity during the reward period but after the sensory cue has been shown to alter learning of a sensory association task (Ford et al, 2022).…”
Section: Bursting In Vivomentioning
confidence: 99%
See 3 more Smart Citations